Numerical simulation study on oxygen transport in the natural circulation process of liquid lead–bismuth eutectic - Xiangdong Wang; Wentao Guo; Shengfei Wang; Haicai Lv; Fang Liu; Zhangpeng Guo (International Journal of Advanced Nuclear Reactor Design and Technology, 2025)
The lead-cooled fast reactor uses liquid lead–bismuth eutectic (LBE) as the coolant. In accident conditions, a passive cooling system is used to remove the heat from the reactor core to avoid meltdown. Therefore, the natural circulation ability of liquid LBE directly affects the inherent safety of the lead-cooled fast reactor. Due to the certain corrosiveness of LBE to the metal pipe wall, oxygen control technology needs to be used to avoid corrosion. So it is of great significance to understand the transport characteristics of oxygen concentration in LBE with natural circulation. In order to study the oxygen transport characteristics of LBE in natural circulation circuit, this article uses FLUENT software to conduct CFD simulation using the oxygen transport model. The mass flow rate of natural circulation under different power conditions in the cold and hot sections was discussed. The effects of different LBE temperatures and different inlet velocities of the expansion tank on oxygen transport were discussed in a classified manner. Based on this, the simulated values were fitted to obtain the Sh number relationship (oxygen transport relationship) for different flow patterns in the expansion tank under natural circulation conditions. The simulation results can provide a reference for the design and research of lead-cooled fast reactors.